Strategi Pembelajaran Bahasa dan Sastra Indonesia di Sekolah Dasar: Peran Guru dalam Menyikapi Kurikulum Tingkat Satuan Pendidikan - Kushartanti, Kushartanti (Wacana, Journal of the Humanities of Indonesia, 2007)
Teaching Indonesian in formal schools today is regarded as a challenge by many Indonesian teachers. In a country like Indonesia, in which language situation is very complex due to many languages and dialects (and also the fast-growing English usage in big cities), this phenomenon can be understood. Since the country's independence, there have been several curricula-one of them is Kurikulum Berbasis Kompetensi (competence-based curriculum), the newest being Kurikulum Tingkat Satuan Pendidikan (Unit Level of Education-Based Curriculum). The latter seems to be regarded as the most ideal curriculum, because it can be adjusted to the regions' policy. The problems are that there are still Ujian Nasional (national examination) and that the 'readability' of the curriculum is still a big question for many teachers. This paper is focused on the elementary school teacher's strategies on applying the curriculum. This paper also discusses the curriculum, some principles on language learning, and the emergence of literary matters.